The Development of Wellness Tourism in Curug Wadas Malang, Mangkang, Semarang - Hendro Prabowo; Awal Prasetyo; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to develop Curug Wadas Malang in Mangkang as a wellness tourism destination within Semarang City. Utilizing field research, the study involved direct observation and interaction with individuals in their natural environment, as outlined by Sugiyono (2018). Observations were conducted in the Curug Wadas Malang forest area, alongside interviews with forest rangers, local residents, and Indonesian Red Cross (PMI) officers. This dual approach of simultaneous observations and interviews facilitated comprehensive data collection.In addition to fieldwork, a thorough literature review was undertaken to explore existing health tourism examples that incorporate natural elements such as forests, rivers, and waterfalls. The data gathered from both the literature and field research were thematically analyzed following the methodology proposed by Braun, Clarke & Hayfield (2022). The analysis revealed four key themes: the potential for wellness tourism at Curug Wadas Malang, the advantages of integrating forest, river, and waterfall elements in wellness tourism, a case study of Hoshinoya Karuizawa in Japan, and another case study from Kaua'i in Hawaii.The findings indicate that Curug Wadas Malang possesses significant natural resources and social capital through Community-Based Disaster Preparedness (CBDP) initiatives led by local communities. Therefore, a community-based tourism approach is recommended. This strategy emphasizes involving local populations in planning and implementing health tourism initiatives, enhancing disaster preparedness efforts while promoting sustainable tourism that benefits the community economically and socially